Author’s Worldview in the Context of Gender Analysis of Literary Works (based on the Novel Green Tent by L. Ulitskaya) - Nurgali К.Р.; Uaisbayeva А.Г. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
This article examines the features of the author’s concept of creating an artistic world in the context of gender issues, as the issue of «women’s writing» in the modern stage of literary studies is one of the relevant ones, as evidenced by the diversity of theoretical works considering feminist literature. The novel «Green Tent» by Lyudmila Ulitskaya was chosen as the object of study, as this author is one of the promising contemporary writers. The purpose of this study is to identify the features of the artistic world of the work from the point of view of the author’s positioning in the context of gender issues. To successfully achieve this goal, we collected material regarding “women’s writing” in the context of changes in the literary process, analyzed the novel of the author chosen as the object of study from the perspective of the use of various linguistic means and a comparative analysis of the character system: the differences and similarities of male and female types of characters in a work of art. In the course of the analysis, it was revealed that Ulitskaya uses the linguistic diversity of language, tropes and various connotations, detailed description of the system of characters, and social and axiological aspects of the described era to create an authorial picture of the world.